"We are not only English Jews-we are Jewish Englishmen" The Making of an Anglo-Jewish Identity, 1840-1880 - Abosch-Jacobson, Sara (Academic Studies Press, 2019)
Between 1840 and 1880, a mature, increasingly comfortable, native-born Jewish community emerged and matured in London. The history of this community and the ways it developed are explored in this volume using archival and also contemporary advertising material that appeared in the Jewish Chronicle and other Anglo-Jewish newspapers in these years.